Nurses’ Knowledge regarding Infection Prevention in Neutropenic Patients at Tertiary Cancer Hospital, Nepal (International Journal of Silkroad Institute of Research and Training, 2024)
Background:Neutropenia is one most common risk factor for infection and the leading causes of death in cancer patientsthat may results in unexpected hospitalizations and disruption in treatment plans and regimens.Method: A cross-sectional study was carried out among 100 nurses to assess the knowledge regarding infection preventionin neutropenic patients to those who are working least 6 months in chemotherapy of B.P. Koirala Memorial Cancer Hospital(BPKMCH). A non-probability purposive sampling technique was adopted to select the sample and the data was collectedthrough a structured self- administered questionnaire. Data were analyzed by using Statistical Package for Social Science(SPSS) version 22.Result: The study findings summarized the level of knowledge into three categories where more than half (51%) of therespondents had good level of knowledge, 46% had moderate knowledge and 3% had poor knowledge regarding infectionprevention in neutropenic patients.Conclusion: Though majority of the respondents had good and moderate level of knowledge regarding infection preventionin neutropenic patients but there is still lack of Guideline/Protocol on infection prevention measures and gap in knowledgeregarding daily nursing assessment. So, there is still need to develop and implement infection prevention guidelines/protocols and regular trainings on infection prevention from concern authority of hospital management.